Development of Edu-Monopoly Based on Numeration of Mixed Arization Operation Materials for Elementary School - Via Yustitia; Risma Azizah; Reza Rachmadtullah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Research purposes development This (1) knows the process of developing educational media - based on monopoly numeracy material operation count mixture , (2) knowing eligibility development of edu -monopoly based media numeracy material operation count mixture . (3) knowing implementation and response student against development of edu -monopoly based media numeracy material operation count mix . Research development This adapted from the ADDIE development model (Analysis , Design, Develop, Implementation, Evaluation), but limited to the stage Implementation (Implementation). Data collection method using instrument study questionnaire validation material , questionnaire media validation , and questionnaires response students . Data analysis techniques used in the study This use quantitative data analysis For know eligibility products and analysis descriptive For describe the process and results development product . The result of study This show that (1) product results development of edu -monopoly based media numeracy material operation count mixture developed through four stage that is stage Analyze ( analysis beginning , analysis students , analysis material , analysis objective learning ) , Design ( designing appropriate learning media with need students ), Development ( in the form of product results development of edu -monopoly based media numeracy material operation count mix ), Implementation (trial ) product ). (2) Results of the feasibility test product development through validation media experts get results percentage 79% with “Eligible” category , results validation expert material get results percentage 82.5% with “Eligible” category , then validation Language experts get results percentage 85% with “Eligible” category . Then the results from development edu -monopoly based media products numeracy as Supporter in activity learn on the material operation count mixture For student Class IV. (3) Implementation process media and response games student to product development of edu -monopoly based media numeracy material operation count mixture.